Superlattice nanostructures based on chalcogenide semiconductors - Sipatov (Functional Materials, 2009)
The multilayer chalcogenide semiconductor films with large layer lattice misfit (0.5-13 %) are shown to open the new opportunities for development of one-, two- and three-dimensional superlattice nanostructures. The superconductivity has been revealed for the first time in two-dimensional (dislocational) superlattices, the presence of periodic networks of misfit dislocations at interfaces being directly responsible for the superconductivity. The spectra of 1 uminescence from quantum dots have been discovered for the first time in three-dimensional PbSe-PbS superlattices, the dots being formed by structure modulations from periodic misfit dislocations along the layer interfaces and composition modulations in the orthogonal direction. The resonance tunneling of electrons via ferromagnetic EuS barriers was found for one-dimensional (compositional) superlattices. The antiferromagnetic interlayer coupling of magnetic EuS layers via non-magnetic PbS and YbSe spacers has been found for the first time in semiconductor superlattices. Such coupling is observed for unusual wide range of spacer thicknesses for narrow-gap PbS semiconductor (from 0.4 nm to 40 nm) and wide-gap YbSe (from 1 nm to 3 nm). Показано, що використання багатошарових плівок халькогенідних напівпровідників з невідповідністю граток суміжних шарів у широких межах (0,5-13 %) відкриває нові можливості для створення одно-, дво- та тривимірних надграткових наноструктур. Для двовимірних (дислокаційних) надграток вперше виявлено надпровідність, пов'язану з присутністю періодичних сіток дислокацій невідповідності на міжфазних межах. Для тривимірних надграток PbSe-PbS вперше знай:дено спектри люмінесценції з квантових точок, утворених модуляцією структури періодичними дислокаціями у площині композиції та модуляцією складу в ортогональному напрямку. Для одновимірних (композиційних) надграток виявлено резонансне тунелювання електронів через феромагнітні бар'єри EuS, а також антиферомагнітне упорядкування магнітних шарів, зумовлене їх взаємодією через діамагнітні прошарки PbS та YbSe. Таке упорядкування спостерігається для незвично великого діапазону товщини прошарків вузькозонного напівпровідника PbS (від 0,4 до 40 нм) та широкозонного YbSe (від 1 до 3 нм). Показано, что использование многослойных пленок халькогенидных полупроводников с несоответствием решеток соседних слоев в широких пределах (0,5-13 %) открывает новые возможности по созданию одно-, двух- и трехмерных сверхрешеточных наноструктур. Для двумерных (дислокационных) сверхрешеток впервые обнаружена сверхпроводимость, которая связана с присутствием периодических сеток дислокаций несоответствия на межфазных границах (отсутствие дислокаций приводит к отсутствию сверхпроводимости). Для трехмерных сверхрешеток PbSe-PbS впервые обнаружены спектры люминесценции из квантовых точек, созданных модуляцией структуры периодическими дислокациями вдоль межфазных границ и модуляцией состава в ортогональном направлении. Для одномерных (композиционных) сверхрешеток обнаружено резонансное туннелирование электронов через ферромагнитные барьеры EuS, а также антиферромагнитное упорядочение магнитных слоев, обусловленное их взаимодействием через диамагнитные прослойки PbS и YbSe. Такое упорядочение наблюдается для необычно большого диапазона толщины прослоек узкозонного полупроводника PbS (0,4-40 нм) и широкозонного YbSe (1-3 нм).